2016
DOI: 10.1097/mbc.0000000000000456
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heat shock proteins and endothelial dysfunction in acute pulmonary embolism

Abstract: We determined the levels of some heat shock proteins (HSP27, HSP70, and HSP90), L-arginine, asymmetric dimethylarginine (ADMA), and symmetric dimethylarginine (SDMA) levels in patients with acute pulmonary embolism. The present case-control study comprised a healthy control group (n = 57) and patients with acute pulmonary embolism (n = 84). HSPs, L-arginine, ADMA, and SDMA levels were measured in all of the cases. The mean age of the control group was 56.72 ± 8.44 years, and the mean age of the patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The required induction of end-othelial dysfunction may be the result of the younger age of our animals because endothelial NO-production decreases with age (Liu et al 1992;Parker et al 2000). Also in humans, endothelial dysfunction is often present both in patients with acute pulmonary embolism, as well as with CTEPH, and correlates with disease severity (Reesink et al 2006;In et al 2016;Chibana et al 2017). In humans, CTEPH prevalence is higher in females (Kirson et al 2011), although male patients typically have a worse prognosis (Chen et al 2018).…”
Section: Animal Modelmentioning
confidence: 99%
“…The required induction of end-othelial dysfunction may be the result of the younger age of our animals because endothelial NO-production decreases with age (Liu et al 1992;Parker et al 2000). Also in humans, endothelial dysfunction is often present both in patients with acute pulmonary embolism, as well as with CTEPH, and correlates with disease severity (Reesink et al 2006;In et al 2016;Chibana et al 2017). In humans, CTEPH prevalence is higher in females (Kirson et al 2011), although male patients typically have a worse prognosis (Chen et al 2018).…”
Section: Animal Modelmentioning
confidence: 99%
“…In the microvasculopathy observed in chronic thromboembolic pulmonary hypertension, pulmonary endothelium cells are known to play a key role, and it has a significant role both in the disease's development and in the targeted treatment . In recent years, pulmonary endothelial dysfunction in acute PTE has gradually become a point of focus, and various studies have reported increasing endothelial dysfunction markers in these groups of patients . According to our review, there is only one study investigating the serum endocan levels in patients with PTE in the literature.…”
Section: Discussionmentioning
confidence: 95%
“…Prospective studies involving gene expression profiling in larger patient cohorts, functional validations, evaluation in real-world settings, and comparison with current methods are warranted before biomarkers can be confidently applied in clinical practice. [12,13] Methods:…”
Section: Introductionmentioning
confidence: 99%